Kelp leads the way! - Testa, Maggie (Ready-to-read. Rising star reader!, 2024)
Kelp's special Unicorn Spark helps him live with his family in the sea and visit his friends in Unicorn Land. But when Kelp's Unicorn Spark makes a mess, he learns how to fix it on his own.